Exposome in IBD: Recent Insights in Environmental Factors that Influence the Onset and Course of IBD. Issue 2 (February 2015) - Rogler, Gerhard; Vavricka, Stephan
Abstract : Abstract: It is generally agreed that environmental factors trigger the onset and cause flares of inflammatory bowel disease. Although we have learned much about genetic susceptibility factors of inflammatory bowel disease in recent years, our knowledge on these environmental factors is limited. The sum of all environmental factors a human is exposed to during lifetime has been termed the exposome. The challenge of investigating the exposome is discussed in this overview. The environmental exposure of a subject causes changes in the intestinal microbiota and subsequently changes the epigenetic imprinting of the mucosa and the associated immune system. Some relevant environmental factors have been investigated in recent years in inflammatory bowel disease and other (auto)inflammatory disease. These factors can be categorized in air pollution, diet, drugs, stress, infections, water pollution, food additives, and lifestyle. Examples from those categories and their potential pathophysiological mechanism are discussed. Abstract : Article first published online 29 October 2014.